FROM STRESS TO SUCCESS: OVERCOMING MENTAL HEALTH CHALLENGES FOR TEACHERS WORKING WITH SLOW LEARNERS - Ifan Ali Alfatani; Mowafg Masuwd; Erfan Habibi; Nuri Firdausiah; Mohammad Samsul Arifin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to analyze the mental health challenges faced by teachers teaching slow learners at Madrasah Ibtidaiyah Nurul Huda Bondowoso and identify effective strategies for addressing them. A qualitative case study approach was used, using in-depth interviews, classroom observations, and analysis of school policy documents. The results indicate that teachers face high levels of emotional distress and stress due to the demands of adapting teaching methods to students' individual needs. While the Madrasah provides emotional and psychological support through counseling services and stress management training, barriers to seeking psychological help remain, including stigma. Collaboration between teachers, parents, and specialists has been shown to improve teaching effectiveness and student well-being. Furthermore, the implementation of adaptive teaching methods plays a significant role in reducing teacher stress levels and increasing slow learner engagement and learning outcomes. In conclusion, holistic support encompassing emotional, social, and pedagogical aspects is necessary to maintain teacher mental health and improve the quality of inclusive education in Madrasahs.